Inequality of opportunity in wealth: Levels, trends, and drivers - Daniel Graeber; Viola Hilbert; Johannes König (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
While inequality of opportunity (IOp) in earnings is well studied, the literature on IOp in individual net wealth is scarce to non-existent. This is problematic because both theoretical and empirical evidence show that the position in the wealth and income distribution can significantly diverge. We measure ex-ante IOp in net wealth for Germany using data from the Socio-Economic Panel (SOEP). Ex-ante IOp is defined as the contribution of circumstances to the inequality in net wealth before effort is exerted. The SOEP allows for a direct mapping from individual circumstances to individual net wealth and for a detailed decomposition of net wealth inequality into a variety of circumstances; among them childhood background, intergenerational transfers, and regional characteristics. The ratio of inequality of opportunity to total inequality is stable from 2002 to 2019. This is in sharp contrast to labor earnings, where ex-ante IOp is declining over time. Our estimates suggest that about 62% of the inequality in net wealth is due to circumstances. The most important circumstances are intergenerational transfers, parental occupation, and the region of birth. In contrast, gender and individuals' own education are the most important circumstances for earnings.
Keywords: D63; J62; D31; J24; 330; Inequality; Wealth; Inequality of Opportunity; Decomposition